Remote Sensing for Geology and Mapping (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Remote sensing science and technology is a strategic emerging interdisciplinary discipline developed on the foundations of Earth science, traditional physics, and modern high technology. It provides humanity with diverse Earth Observation information and remote sensing data products, and has become a critical tool for scientific research in geology and mapping. In recent years, the development of technologies such as Earth big data and multi-satellite networked observation systems has significantly expanded data sources for remote sensing monitoring in geology and mapping, propelling this field into a new phase of advancement. This reprint highlights recent research efforts in the new theories, new technologies, and new applications of remote sensing in geology and mapping. The knowledge and understanding gained from this reprint can be used for the sustainable development of remote sensing in geology and mapping.